Effect of rhodium additive on the reduction behaviour of iron oxide in carbon monoxide atmosphere [Kesan penambahan rodium terhadap tindak balas penurunan ferum oksida di dalam atmosfera karbon monoksida] - Saharuddin T.S.T.; Salleh F.; Samsuri A.; Dzakaria N.; Othaman R.; Kassim M.B.; Mohammad Hisham M.W.; Yarmo M.A. (Malaysian Society of Analytical Sciences, 2024)
Indexed by Scopus